Reorientation of Criminal Sanctions in the New Criminal Code: Harmonization of the Doctrine of Qishash Fiqh Jinayah with the Paradigm of Restorative Justice - Muhammad Rafli Pratomo; Azzriel Al Bari Daulay; Dian Prildani Pasaribu; Trio Pranata Ginting (ISNU Sumatera Utara, 2026)
The enactment of Law Number 1 of 2023 on the Criminal Code marks a paradigm shift in Indonesian criminal law from a colonial retributive model toward corrective and restorative justice. This study examines the relevance of the doctrine of Qishash within Fiqh Jinayah as a philosophical and practical foundation for the implementation of restorative justice in Indonesia. Using a normative-juridical method with conceptual and comparative approaches, the study analyzes the mechanisms of al-'afw (forgiveness) and diyat (compensation) in homicide cases, which position victims as the primary rights-holders in dispute resolution. The findings indicate that the regulation of conditional capital punishment under Article 100 of Law No. 1 of 2023 substantially aligns with the Islamic principle of suspending execution to allow islah (reconciliation). Furthermore, classical juristic debates on the imposition of ta'zir after forgiveness provide a theoretical basis for maintaining public order. The study concludes that Qishash represents a comprehensive system for the protection of life and, if integrated prudently, can strengthen the development of a just and humane national criminal law system.